2018
DOI: 10.1101/464081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Promoter-intrinsic and local chromatin features determine gene repression in lamina-associated domains

Abstract: It is largely unclear whether genes that are naturally embedded in lamina associated domains (LADs) are inactive due to their chromatin environment, or whether LADs are merely secondary to the lack of transcription. We show that hundreds of human promoters become active when moved from their native LAD position to a neutral context in the same cells, indicating that LADs form a repressive environment. Another set of promoters inside LADs is able to "escape" repression, although their transcription elongation i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…TIRs in H3K27me3 domains also frequently overlapped active histone marks, especially H3K4me3 and H3K4me1. Taken together, our results are consistent with recent reports that transcription start sites within heterochromatin can escape repression (Leemans et al 2018).…”
Section: Heterochromatin Domains Frequently Harbor Tirssupporting
confidence: 93%
“…TIRs in H3K27me3 domains also frequently overlapped active histone marks, especially H3K4me3 and H3K4me1. Taken together, our results are consistent with recent reports that transcription start sites within heterochromatin can escape repression (Leemans et al 2018).…”
Section: Heterochromatin Domains Frequently Harbor Tirssupporting
confidence: 93%
“…Moreover, recent studies have demonstrated that both H3K9me2/3 and H3K27me3 are involved in LAD organization 13,18,19,22 . These findings, along with direct comparisons to Hi-C data and A/B compartment organization, have confirmed that the LADs represent a repressive genome compartment 14,[23][24][25][26] . LADs are immediately flanked by active promoters, highlighting the stark delineation between repressed LAD domains and adjacent active regions.…”
Section: Introductionsupporting
confidence: 60%
“…In support of this notion, a recent genome-wide study of autonomous promoter activity has shown that LAD promoters indeed display differential sensitivity towards the local chromatin features [25]. This study employed the random integration of LAD promoters into the genome to determine the effect of chromatin context on promoter activity, and identified a class of ‘escaper’ promoters that are relatively insensitive to the LAD chromatin environment [25]. The ability of these elements to escape their repressive surroundings does not directly correlate with promoter strength, but likely depends on inherent DNA sequence features.…”
Section: Transcriptional Repression At the Nlmentioning
confidence: 97%
“…The differences between these and multiple other tethering approaches may relate to intrinsic differences in promoter sensitivity to embedding within the repressive LAD chromatin environment [23,24]. In support of this notion, a recent genome-wide study of autonomous promoter activity has shown that LAD promoters indeed display differential sensitivity towards the local chromatin features [25]. This study employed the random integration of LAD promoters into the genome to determine the effect of chromatin context on promoter activity, and identified a class of ‘escaper’ promoters that are relatively insensitive to the LAD chromatin environment [25].…”
Section: Transcriptional Repression At the Nlmentioning
confidence: 99%